HAK AKSES ATAS ENERGI BERSIH DAN TERJANGKAU SEBAGAI BENTUK PEMENUHAN HAK ATAS TEMPAT TINGGAL YANG LAYAK - Erna Dyah Kusumawati; Sasmini Sasmini (Veritas et Justitia, 2023)
Access to clean and affordable energy has become a persistent problem faced by countries worldwide. The peak increase in oil prices experienced in a few decades has made it difficult for the low incomes to access clean energy. At present, many people in rural areas still use wood as fuel for cooking. Indoor wood-burning activities might cause air pollution and triggers respiratory problems. Employing a conceptual approach, this article examines the debate on the concept of moral and legal right of the right to clean and affordable energy under international law. Moreover, it analyses the correlation and the importance of such right for the fulfilment of the right to adequate housing and how states adhere to it. The research finds that there is yet any legal instruments directly recognising the right to clean and affordable energy. Nevertheless, there is plenty recognition of the importance of energy as vital element for fulfilling other human rights, such as the right to adequate housing. It is found that states have recognised the utmost influence of energy on achieving economic and social goals. However, current state practices heavily depend on soft law and show their commitment to facilitate and fulfil the moral right to clean and affordable energy. Integrating human rights principles, norms, and standards into legal rights and policies on energy development plan are indeed crucial. Such integration will enable the recognition of energy as an entitlement, which will place energy as a precondition that must be provided as essential services to enable adequate life of inhabitants.